2018
DOI: 10.1126/science.aar6941
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal stability of nanograined metals below a critical grain size

Abstract: The limitation of nanograined materials is their strong tendency to coarsen at elevated temperatures. As grain size decreases into the nanoscale, grain coarsening occurs at much lower temperatures, as low as ambient temperatures for some metals. We discovered that nanometer-sized grains in pure copper and nickel produced from plastic deformation at low temperatures exhibit notable thermal stability below a critical grain size. The instability temperature rises substantially at smaller grain sizes, and the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 298 publications
(124 citation statements)
references
References 34 publications
11
112
0
Order By: Relevance
“…Adopting low energy boundaries such as twin boundaries and low-angle GBs, which are more reluctant to recrystallize (8)(9)(10), is an alternative stabilization strategy without changing material chemistry. Our recent study revealed that nanograined metals with random GBs can be stabilized through GB relaxation (11)(12)(13). Both thermal and mechanical stability of very fine nanograins in a number of facecentered cubic (fcc) metals are enhanced considerably, originating from a deformation-induced autonomous GB relaxation to lower energy states through emission of stacking faults or twins from the boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting low energy boundaries such as twin boundaries and low-angle GBs, which are more reluctant to recrystallize (8)(9)(10), is an alternative stabilization strategy without changing material chemistry. Our recent study revealed that nanograined metals with random GBs can be stabilized through GB relaxation (11)(12)(13). Both thermal and mechanical stability of very fine nanograins in a number of facecentered cubic (fcc) metals are enhanced considerably, originating from a deformation-induced autonomous GB relaxation to lower energy states through emission of stacking faults or twins from the boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that in Cu with a purity of 99.9 to 99.99% and a deformation strain below 100%, annealing twins are usually formed upon annealing at a temperature ranging from 473 to 523 K (19,20). Unfortunately, this temperature window is well above that for nanograin coarsening in Cu, typically 393 to 450 K for grain sizes of 50 to 200 nm (11). In other words, as nanograins are heated, nanograin coarsening through GB migration occurs before formation of annealing twins.…”
Section: Introductionmentioning
confidence: 99%
“…These same authors provided confirmation of H-P grain size strengthening via separately reported hardness measurements. In related research on nano-grained copper and nickel materials, Zhou et al have given emphasis to the importance of establishing thermal stability of the grain boundary structures in such materials [36]. Otherwise, Figure 4 shows v* to be an effective monitor for detecting the onset of grain size weakening, for example, in line with the determination of material creep behavior as described in a previous report by Armstrong et al [37].…”
Section: Crystal Size-dependent Strain Rate Sensitivitymentioning
confidence: 53%
“…Compared with Ni/Si-NPA, the pillars of sample A maintained their shapes and became slightly shorter after CVD growth, as shown in figure 2 c . The change of the texture and morphology might be due to the recrystallization and size growth of nc -Ni at 1000°C during the CVD process, which was a considerably higher temperature than the highest reported stability temperature of Ni nanograins at 900°C [22,23]. The recrystallization and growth size of nc -Ni also corresponded to the narrower full width at half maximum of the Ni XRD peaks in sample A.…”
Section: Resultsmentioning
confidence: 97%